Brain Myths Exploded: Lessons from Neuroscience. Episode 24,Does Technology Make You Stupid?. - Viskontas, Indre; Kanopy (Firm). ([San Francisco, California, USA] : Kanopy Streaming, 2019)
In this final lecture, ponder several prevalent myths about the relationship between technology and the brain. Among these: smartphones are killing our attention spans, social media is addictive (and leads us to be less social), computers make us less intelligent, and search engines are destroying our memory.
Indre Viskontas
Originally produced by The Great Courses in 2017.
In English
Keywords: Educational films